Conflict of Interests: Medical Ethics - Syed Qarib Abbas Shah (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2012)
Virtues and vices, prevalent in a community do affect almost every person in the society. Though everybody is aware of these values, but their practice depends upon the beliefs and circumstances. Every educated person of the society understands the morality. The medical persons are more sagacious to practice this morality ie Medical Ethics, the doctrine of the duties oflife and the doctrine of one’s own duties. In our society in the hospitals, clinics and Institutes, one can witness wrangling, hardship, disputes, misbehaviour and quarrels of patients, their attendants with the health care persons. The aggressive attitude of the community reflects intolerance. Is it all that the clinicians are distracted from the medical ethics? Are they no more unbiased and detached in their routine medical practice. Is there conflict of interest between clinician and patients? Medical ethics and conflict of interests are to be addressed with maximum determination. In this article some principles of the medical ethics and conflict of interest are discussed with brief history of medical ethics.